Involvement of pharmacist-reviewed urine cultures and sexually transmitted infections in the emergency department reduces time to antimicrobial optimization. (19th May 2020) - Olson, Amber; Feih, Jessica; Feldman, Ryan; Dang, Cathyyen; Stanton, Matthew
Abstract: Purpose: To streamline workflow of the culture review process in the emergency department (ED), a transition from a nurse-driven to a pharmacist-initiated process was implemented. Methods: This was a single-center retrospective study conducted at an adult urban level 1 trauma academic medical center. The pharmacist-initiated culture review process was compared to the previous nurse-initiated process. The primary objective was time from final culture result to patient contact by an advanced practice provider. Secondary objectives included incidence of treatment failure and hospital admission within 30 days of ED visit. Results: A total of 283 patients met inclusion criteria: 144 patients in the pre-intervention group and 139 patients in the postintervention group. Patients were contacted a median time of 15.7 hours (95% confidence interval [CI], 9.88-18.83) earlier for definitive urinary tract infection antibiotic therapy and 46.7 hours (95% CI, 33.34-61.62) earlier for definitive sexually transmitted infection therapy in the pharmacist-initiated workflow compared to the nurse-initiated workflow ( P < 0.001). Treatment failure occurred in 0.01% of patients in the postintervention group and 6.3% in the pre-intervention group ( P = 0.01). Hospital admission within 30 days of the ED visit occurred in 0% of patients in the postintervention group and 4.2% in the pre-intervention group ( P = 0.03). Conclusion: Pharmacist-initiated culture review in the ED at an academic medical center reduced time from final culture to patient contact for optimal antibiotic therapy and decreased hospital admission and treatment failure rates. A change in the culture review workflow involving pharmacists appears to have a positive impact on clinical outcomes.